Identifying the influence of traffic management on vehicle emissions and the distribution of air dispersion in the Makassar port area - Ariati, Ariati; Arifin, Muhammad Zainul; Sutikno, Fauzul Rizal; Bowoputro, Hendi; Miftahulkhair, Muh (Eastern-European Journal of Enterprise Technologies, 2024)
Air pollution in several cities in Indonesia has been increasing significantly over the years. One of the primary triggers is the rise in motor vehicle activity. This increase is due to the improving economic conditions and the decreasing prices of motor vehicles. Vehicles produce various types of pollutants. The pollutants contained in vehicle exhaust gas are carbon monoxide (CO), nitrogen oxide (NOx), sulfur (SOx) and dust (PM). One of the busiest areas for motorized vehicle activity is the Makassar Port Area, which is the largest port in Eastern Indonesia. This area experiences high vehicle activity. The emissions reviewed in this research are CO (carbon monoxide) and NOX (nitrogen oxide) in the Makassar Port Area which is located on Jalan Nusantara, Jalan Sulawesi, Jalan Siswa Army, Dr. Wahidin Jalan Sudirohusodo, Jalan Sangir, Jalan Kalimantan, Jalan Sarappo, Jalan Banda, and Jalan Butung. This research utilizes historical data on traffic volume, wind speed and direction, air humidity, air temperature, air pressure, solar radiation, cloud cover and surface height. Air dispersion analysis was carried out using AERMOD software. The highest emissions obtained were 67,121 μg/m3 for CO and 9,570 μg/m3 for NOx under existing conditions and after implementing traffic management measures, the highest emissions were reduced to 45,737 μg/m3 for CO and 7,217 μg/m3 for NOx. These results conclude that traffic management can reduce air pollution. Air dispersion is not only influenced by vehicle volume but also meteorological factors. This can be seen in the dispersion results. Where, the conditions before and after traffic management showed differences in terms of the distribution of air dispersion